The effect of hot or cold water immersion on isometric strength training - Burke, D. G.; MacNeil, S. A.; Holt, L. E.; MacKinnon, N. C.; Rasmussen, R. L. (The Journal of Strength and Conditioning Research, 2000)
The purpose of this study was to compare the changes in force production resulting from isometric strength training, in combination with 3 different treatment conditions: control, cold water immersion, and hot water immersion. Forty-five noninjured subjects between the ages of 18 and 25 were randomly assigned to 1 of 3 groups: control, cold, or hot. Subjects exercised only their right lower limb using static muscular contractions, consisting of 1 set of 4 repetitions, for 5 consecutive days. On the first day, after a few warm-up contractions, subjects were measured for maximum isometric force production (MIFP) of the hip extensor (HE) musculature at the end range of hip flexion. After this initial measure, subjects underwent their respective treatments. Control subjects rested for 10 minutes, subjects in the cold group stood in a cold water bath (8 ± 1° C) immersed up to their gluteal fold for 10 minutes, and subjects in the hot group stood in a hot water bath (43 ± 1° C) immersed up to their gluteal fold for 10 minutes. After the last training session, subjects were again measured for MIFP of the HE musculature at end range. Group results were assessed using a two-way analysis of variance procedure, comparing changes in isometric force production from pre- to posttest and between sexes. Multiple comparisons were performed to determine where significant (p < 0.05) differences occurred. All 3 groups had significant improvements in HE isometric force production (pre to post). The increase in MIFP for the cold group was significantly greater than that of the control and hot groups. Sex differences were evident in the cold group only, with men experiencing greater increases.